Preoperative Elective Bowel Preparation In Children With Polyethylene Glycol Versus Polyethylene Glycol and Mannitol - A Comparative Study - Islam, Md Tawhidul; Huq, Md Ashraf Ul; Hasina, Kaniz; Hossain, Tahmina; Das, Sahadeb Kumar; Masud, Sadruddin Al; Das, Bipul Bhusan; Islam, KM Shaiful (Journal of Dhaka Medical College, 2023)
Background: Oral mechanical bowel preparation is a routine practice prior to colorectal surgery in many centers. Virtually all colorectal surgeons consider a mechanically cleansed and empty bowel as one of the prerequisites for a safe colonic resection and anastomosis. Various agents had been used in different centers in mechanical bowel preparation. Methods: A comparative prospective interventional analysis of preoperative elective bowel preparation in children with polyethylene glycol versus polyethylene glycol and mannitol was conducted on 60 children underwent elective GIT surgery between July 2014 and June 2016. The patients were allocated into 2 groups by simple random sampling, 30 in each group. Children of 6 months to 14 years were selected as study population. In group I, PEG was given per orally or through nasogastric tube at the rate of 1.5 gm powder/kg/dose, in group II, PEG & Mannitol were given orally or via nasogastric tube. PEG was administered as same dose of group I and mannitol 20% at a dose of 10 ml/kg/dose. All patients received prophylactic intravenous antibiotics (ceftriaxone + metronidazole) preoperatively as well as in postoperative period. All children were investigated preoperatively and post operative follow up was recorded. Structured questionnaire was used to collect information regarding preoperative status and post operative follow up. Statistical assessments were done by SPSS version 21. An Ethical clearance had been sought. Results: Sixty children underwent mechanical bowel preparation prior to GIT surgery. 30 with PEG (group I) and 30 with PEG and Mannitol (group II). Our outcome variables were wound infection, anastomotic leakage, and Electrolyte balance. Demographic pattern also evaluated. The age range of both groups was 6-68 months, p value 0.987. In both group male and female were same in number, 16 male and 14 female each in both groups. Wound infection occurred 3 cases (10%) in PEG group and 2 cases in PEG and Mannitol group, p value 0.64. No anastomotic leakage in PEG and Mannitol group and only 1 leakage in PEG group. No Electrolyte imbalance was found in both groups. No mortality was recorded in this study. Conclusions: No significant difference was found between the two study groups in respect of wound infection, anastomotic leakage and electrolyte balance. Ingestion of two drugs did not have any better outcome. So, mannitol can be omitted in MBP in children. J Dhaka Med Coll. 2022; 31(1) : 29-36